1998
DOI: 10.1002/j.1552-4604.1998.tb04437.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Safety of Calcipotriene 30 g Per Day in Patients with Psoriasis: A Parallel Group, Vehicle‐Controlled Study

Abstract: Elevated blood and urine calcium levels have been reported with the use of high doses of calcipotriene ointment in patients with psoriasis. The objective of this study was to evaluate key measures of calcium metabolism in patients with psoriasis under supervised dosing conditions in a vehicle-controlled study. Of the 24 patients enrolled, 12 each were administered 15 g of ointment containing calcipotriene or vehicle twice a day for 14 days. Blood and urine samples and 24-hour urine collections were obtained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Concerning safety, the research focused on hypercalcemia and skin atrophy. Safety was the main topic of seven articles 36–42 . No case of hypercalcemia was reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning safety, the research focused on hypercalcemia and skin atrophy. Safety was the main topic of seven articles 36–42 . No case of hypercalcemia was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Safety was the main topic of seven articles. [36][37][38][39][40][41][42] No case of hypercalcemia was reported. Three other studies [43][44][45] reported transient hypercalcemia without any clinical implication, except in two patients for whom the topical vitamin D analogue was stopped.…”
Section: Topical Steroidsmentioning
confidence: 99%
“…1). A total of 30 studies were performed in patients with plaque psoriasis, 19 studies evaluated VDS, 6–24 11 studies evaluated VD alone, 25–35 3 studies focused on quality of life, 8,36,37 7 studies focused on tolerability 10,38–43 . In addition nine studies on VD or VDS focused on scalp psoriasis, 44–52 two on VD focused on intertriginous psoriasis 53,54 …”
Section: Resultsmentioning
confidence: 99%
“…Safety was the main topic for seven studies 10,[38][39][40][41][42][43] and was also studied in 14 randomized controlled trials. Three studies focused on skin atrophy.…”
Section: Safetymentioning
confidence: 99%
“…In a trial performed by Blum et al [11], 24 patients with moderate to extensive psoriasis were randomised to treatment with either 210 g calcipotriol ointment (50 µg/g) per week or the vehicle for 2 weeks without the induction of either hypercalcaemia or hypercalciuria.…”
Section: Introductionmentioning
confidence: 99%